2020
DOI: 10.47577/tssj.v4i1.99
|View full text |Cite
|
Sign up to set email alerts
|

The elements of political communication on Facebook

Abstract: In its role as a tool that facilitates participation, Facebook acts as a channel of political communication with different mechanisms than traditional media. At the same time, Facebook offers new means of receiving the audience, characterized by a targeting of the very good target audience. The Facebook page of a political party facilitates interaction and political participation, making possible a two-way communication model and facilitating increased political participation of public opinion. The platform is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a sense before sharing a post, the buzzer is also helped by several people with different job desks. As the scheme below: Political Buzeer Activities with Keywords on Twitter Support Anies Baswedan, In the keyword Support Anies Baswedan on twitter penelti found 1156 twett dated December 6, 2021, in finding data researchers used the help of Netlytic.org in retrieving data on twitter and found Preview 1156 data twett (Tasente, 2020). The researchers found that bot or buzzer accounts numbered 150, this account was created in 2021 when the topic of declaration (Xie, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sense before sharing a post, the buzzer is also helped by several people with different job desks. As the scheme below: Political Buzeer Activities with Keywords on Twitter Support Anies Baswedan, In the keyword Support Anies Baswedan on twitter penelti found 1156 twett dated December 6, 2021, in finding data researchers used the help of Netlytic.org in retrieving data on twitter and found Preview 1156 data twett (Tasente, 2020). The researchers found that bot or buzzer accounts numbered 150, this account was created in 2021 when the topic of declaration (Xie, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Anies Baswedan's support network is interesting because the results of relatively low centralization (0403200) show that it is not the dominant actor on social media who directs Twitter conversational content to users. Meanwhile, the high modularity of 0.366800 indicates that the large number of important actors scattered in clusters (Tasente, 2020). Table 1 data shows that Support Anies Baswedan has successfully conducted a digital opinion movement from among Twitter netizens who expressed opinions about the support of net citizens in support to Anies Baswedan in the 2024 presidential election.…”
Section: Discussionmentioning
confidence: 99%
“…We analyse posts on Facebook, which is one of the most frequently used venues for politicians to communicate with their audiences directly in Slovakia. There is little to no moderation of Facebook and communication is immediate (Tasente, 2020). Thus, in times of crises, Facebook posts capture immediate positions of the actors.…”
mentioning
confidence: 99%